Bargaining in legislature: number of parties and ideological polarization (2007)
There is a common perception in the political economy literature that a larger number of parties makes it more difficult and more expensive - in terms of pork barrel programs - to implement policy-changes in a legislature. This paper proves that this perception is not necessarily true. The driving idea behind this result is that the number of parties should matter for legislative outcomes only to the extent that the ideological polarization between them is high. The model developed in this paper shows that it can be cheaper - in terms of pork barrel programs-, and also more likely, for a government party to negotiate its preferred public policy with several parties that are less polarized than with a few parties that are strongly polarized.